Perceived service quality and visitors' sustainable visit intentions in theme parks: empirical analysis on the THEMEQUAL scale - Luo, Jingjing; Li, Xiang (Frontiers in Sustainable Tourism, 2024)
Theme parks, as indispensable commodities within the tourism industry, wield significant influence in fostering local and national economic development. However, despite their crucial role, there remains a dearth of comprehensive research concerning the determinants of theme park visits. Employing the THEMEQUAL scale, this study uses an ordered logit model and in-depth interview method to investigate the effects of service quality on visitors' sustainable visit intentions (SVIs). Results show service quality is the most pivotal determinant shaping SVIs, and effects are moderated by COVID19, i.e., a reduced emphasis on service quality in bolstering visitors' sustainable visit inclinations during this pandemic. Specially, assurance and courtesy of staff delivering their confidence markedly influence visitors' perceptions. This research contributes to a comprehensive interplay between service quality, COVID19 and visitors' SVIs, providing reference for policy makers and managers to develop theme park recovery policies in the post pandemic era.